MiRNA-1/133a clusters regulate adrenergic control of cardiac repolarization. - Johannes Besser; Daniela Malan; Katharina Wystub; Angela Bachmann; Astrid Wietelmann; Philipp Sasse; Bernd K Fleischmann; Thomas Braun; Thomas Boettger (PLoS ONE)
The electrical properties of the heart are primarily determined by the activity of ion channels and the activity of these molecules is permanently modulated and adjusted to the physiological needs by adrenergic signaling. miRNAs are known to control the expression of many proteins and to fulfill distinct functions in the mammalian heart, though the in vivo effects of miRNAs on the electrical activity of the heart are poorly characterized. The miRNAs miR-1 and miR-133a are the most abundant miRNAs of the heart and are expressed from two miR-1/133a genomic clusters. Genetic modulation of miR-1/133a cluster expression without concomitant severe disturbance of general cardiomyocyte physiology revealed that these miRNA clusters govern cardiac muscle repolarization. Reduction of miR-1/133a dosage induced a longQT phenotype in mice especially at low heart rates. Longer action potentials in cardiomyocytes are caused by modulation of the impact of β-adrenergic signaling on the activity of the depolarizing L-type calcium channel. Pharmacological intervention to attenuate β-adrenergic signaling or L-type calcium channel activity in vivo abrogated the longQT phenotype that is caused by modulation of miR-1/133a activity. Thus, we identify the miR-1/133a miRNA clusters to be important to prevent a longQT-phenotype in the mammalian heart.